2000
DOI: 10.1538/expanim.49.39
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of Human Xenotransplantable Tumor with Mouse Hepatitis Virus by Implantation in Nude Rat: A Case Report.

Abstract: Abstract:A human tumor xenograft contaminated with mouse hepatitis virus (MHV) was implanted in a nude rat in order to decontaminate the tumor line. The decontamination failed in the first trial, but succeeded in the second trial. The difference between the two trials was the duration of implantation of the tumor in the nude rat, i.e., 12 days in the first and 24 days in the second trial. Duration of implantation might be a factor in the decontamination of transplantable tumors infected with MHV by passaging i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…There are numerous reports of contamination of tumor cell lines with lymphocytic choriomeningitis virus (LCMV; Bhatt et al 1986;Dykewicz et al 1992), mouse hepatitis virus (MHV 1 ; Takakura et al 2000), lactate dehydrogenase-elevating virus (LDHV 1 ; Chen and Plagemann 1997), mouse parvovirus (MPV 1 ; Garnick 1996), and retroviruses (Suzuki et al 1977). Both the zoonotic potential (Bowen et al 1975) and a recently reported endemic infection (Ike et al 2007) of LCMV underscore the importance of continued surveillance for this organism.…”
Section: Cell Linesmentioning
confidence: 99%
“…There are numerous reports of contamination of tumor cell lines with lymphocytic choriomeningitis virus (LCMV; Bhatt et al 1986;Dykewicz et al 1992), mouse hepatitis virus (MHV 1 ; Takakura et al 2000), lactate dehydrogenase-elevating virus (LDHV 1 ; Chen and Plagemann 1997), mouse parvovirus (MPV 1 ; Garnick 1996), and retroviruses (Suzuki et al 1977). Both the zoonotic potential (Bowen et al 1975) and a recently reported endemic infection (Ike et al 2007) of LCMV underscore the importance of continued surveillance for this organism.…”
Section: Cell Linesmentioning
confidence: 99%
“…For example, MHV contamination of a human tumor xenograft that was maintained in nude mice (the source of infection) was eliminated by passage in nude rats for 24, but not 12 days (Takakura et al 2000). It requires selecting the minimal number of breeding founders possible, isolating them from the infected colony of mice, isolating them from each other, and building up the rederived colony in isolation.…”
Section: B Control Of Mhv In Mouse Populationsmentioning
confidence: 99%